Meaningful History Learning through the Contextual Teaching and Learning (CTL) Approach Based on Otanaha Fortress - Ismaul Fitroh; Moh. Imron Rosidi (Jurnal Ragam Pengabdian, 2025)
History education plays an important role in building historical awareness, cultural identity, and character among students. However, history teaching practices in schools are still dominated by memorisation of facts and chronology, making them less meaningful and contextual. An approach to learning is needed that can relate historical material to the real lives of students. The Contextual Teaching and Learning (CTL) approach is a relevant alternative, especially through the use of local historical sites. This study aims to examine meaningful history learning through the CTL approach based on the Otanaha Fort as a source of local history learning. This study uses a qualitative approach with a literature study method of articles and books published between 2017 and 2025 that are relevant to history learning, CTL, and the utilisation of historical sites. Data analysis was conducted using content analysis techniques. The results of the study indicate that the application of CTL based on Otanaha Fort is capable of creating contextual and meaningful history learning through authentic learning experiences. The utilisation of local historical sites also strengthens historical understanding, instils local wisdom values, and builds the identity and character of students.